2010
DOI: 10.1002/adem.200900222
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Electrospun Mullite Nanofibers

Abstract: Mullite (3Al 2 O 3 Á2SiO 2 ) is well-known as superior engineering ceramic materials owing to its relatively high chemical stability, good refractory properties, high temperature mechanical strength, and low thermal expansion coefficient. [1,2] Fabrication of continuous mullite nanofibers is highly desired because it is an important candidate used as reinforcement of metals, ceramics, and resins. [3,4] Several traditional methods such as sol-gel, melt spinning, and solution spinning methods have been used to f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 15 publications
1
5
0
1
Order By: Relevance
“…This diameter reduction is due to the burning-out of PVC followed by the densification and mullitization processes. Studies [4,6,8,9] on electrospinning of mullite obtained fibers with diameters ranging from 85 nm up to 1mm, indicating that the confidence interval of the mean achieved by SBS in this work (788 up to 860 nm) is in agreement with electrospinning technology.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…This diameter reduction is due to the burning-out of PVC followed by the densification and mullitization processes. Studies [4,6,8,9] on electrospinning of mullite obtained fibers with diameters ranging from 85 nm up to 1mm, indicating that the confidence interval of the mean achieved by SBS in this work (788 up to 860 nm) is in agreement with electrospinning technology.…”
Section: Resultssupporting
confidence: 83%
“…The production of mullite fibers, mostly nanometric and submicrometric fibers, has attracted considerable interest of many technological sectors, because of the excellent properties they exhibit and the large number of applications, ranging from reinforcements for metals, ceramics, and polymers, high temperature structural materials, high temperature plasticizing structural ceramics and insulating systems to membrane technology [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…A refratariedade é a propriedade que o material tem de suportar altas temperaturas sem se deformar ou fundir. Dentre as diversas aplicações da mulita em materiais refratários, destacam-se: cadinhos, peças de isolamentos térmicos, revestimentos de fornos e reatores (para altas temperaturas), matriz e reforço de material compósito, componentes de motores de turbina, vedação elástica em altas temperaturas, catalisadores, membranas de filtração, acessórios para aeronaves espaciais e materiais leves, entre outras [17,18]. Diante desse contexto, este trabalho teve como objetivo avaliar o efeito da composição, tempo de maturação e da temperatura nas propriedades físico-mecânicas de peças cerâmicas obtidas a partir de formulações à base de argilas para uso na fabricação de materiais refratários mulíticos.…”
Section: Introductionunclassified
“…In Zadeh's work, electrospun mullite nanofibers derived from mullite monophasic sol exhibited a uniform microstructure when the sintering temperate was below 1200°C; however, when the sintering temperature increased to 1400°C, mullite fibers showed a porous structure due to the growth of mullite grains. In Lin's work, mullite fibers derived from monophasic sol exited a rough surface when the sintering temperature was only 1200°C. Compared to the mullite fibers derived from monophasic sols, fibers in our work derived from a diphasic sol exhibited a smooth surface even when the sintering temperature was 1400°C (Figure G1) and the mullite grain size in mullite fibers after sintering at 1500°C is only about 100 nm (Figure C), which is similar to that of mullite fibers fabricated by the sol‐gel method (commercially Nextel 720 fibers and laboratory‐produced mullite fibers) .…”
Section: Resultsmentioning
confidence: 99%
“…Although many groups, such as Lin, Zadeh, and Peng, have successfully fabricated nanoscale mullite fibers by electrospinning a monophasic mullite sol, the results indicated that mullite nanofibers derived from the monophasic sol cannot be used at high temperatures (higher than 1400°C) due to the dramatic growth of mullite grains and therefore is unsuitable for being used as the starting material for the fabrication of mullite nanofibrous ceramics. Mullite sol can be divided into the monophasic sol and the diphasic sol according to their homogeneity, and the general agreement of the extensive works is that the homogeneity level of mullite sols actually controls the phase transformation sequence, mullite formation temperature, as well as the properties of sintered bodies.…”
Section: Introductionmentioning
confidence: 99%